Abordagens em Monitoramento de Dados: Estratégias aplicáveis a pesquisa clínica acadêmica - Cunegatto, Fernanda Rohrsetzer; Medolago, Natália Bronzatto [UNESP]; Horn, Tiago Stumpf; de Oliveira-Freitas, Vera Lorentz (Tikinet Edicao, 2025)
In recent years, the increase in the number and complexity of clinical studies has posed significant challenges in overseeing and ensuring the quality of these trials. This article explores various monitoring approaches in clinical trials, discussing the importance of robust monitoring plans, global standardization of procedures, and the integration of advanced technologies. The discussion covers both regulatory-driven and academic-initiated studies, highlighting the specific challenges faced by each type. Additionally, the article examines the role of ethics committees, the importance of inter-institutional collaboration, and practical solutions that can be implemented to enhance the efficiency and quality of clinical studies. The final considerations emphasize that adopting effective monitoring approaches can significantly transform clinical and academic research, promoting important advancements in public healt.